Comparison of Bivalirudin and Heparin in Patients Undergoing Percutaneous Coronary Intervention: A Retrospective Analysis - Khan, Farhat Ullah; Akhtar, Syed Ahsan; Afzal, Zeeshan; Ayub, Asfandyar; Ejaz Ullah (Indus Journal of Bioscience Research, 2025)
Introduction: Anticoagulation must be optimized for both thrombotic and bleeding events in order to determine the risk of percutaneous coronary intervention (PCI). UFH or unfractionated heparin and bivalirudin are classical agents for use in in-patient treatment with some differences in safety and efficacy. Objective: The aim of the study was to evaluate the safety and effectiveness of bivalirudin against UFH for patients undergoing PCI at Department of Cardiology, Hayatabad Medical Complex, Peshawar. Materials and Method: The study involved 320 patients who underwent PCI in the period from July, 2023 to December, 2023. The subjects were further sub-grouped based on the anticoagulant they received, either bivalirudin or UFH. Major adverse cardiac events and bleeding events were also compared and analyzed. Results: Major bleeding was lower in the bivalirudin group in comparison to UFH (4.9% vs. 10.1%, p=0.04); MACE, success of the procedure was similar. Conclusion: Bivalirudin is a safe and effective alternative to UFH in PCI, particularly in patients at high bleeding risk.